2006
DOI: 10.1002/bit.21018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of free ammonia and free nitrous acid concentration on the anabolic and catabolic processes of an enriched Nitrosomonas culture

Abstract: The effects of free ammonia (FA; NH(3)) and free nitrous acid (FNA; HNO(2)) concentrations on the metabolisms of an enriched ammonia oxidizing bacteria (AOB) culture were investigated using a method allowing the decoupling of growth and energy generation processes. A lab-scale sequencing batch reactor (SBR) was operated for the enrichment of an AOB culture. Fluorescent in-situ hybridization (FISH) analysis showed that 82% of the bacterial population in the SBR bound to the NEU probe specifically designed for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(85 citation statements)
references
References 27 publications
(39 reference statements)
4
79
0
2
Order By: Relevance
“…Furthermore, it was suggested that the inhibitory effect on energy generation (catabolic processes) and growth processes (anabolic processes) D i s c u s s i o n | 137 should be investigated separately (Vadivelu et al 2006). Simply comparing the overall substrate utilization rates, as conducted in our study, might have seriously under-estimated the inhibitory effects, certainly in relation to growth inhibition.…”
Section: Salt)mentioning
confidence: 88%
“…Furthermore, it was suggested that the inhibitory effect on energy generation (catabolic processes) and growth processes (anabolic processes) D i s c u s s i o n | 137 should be investigated separately (Vadivelu et al 2006). Simply comparing the overall substrate utilization rates, as conducted in our study, might have seriously under-estimated the inhibitory effects, certainly in relation to growth inhibition.…”
Section: Salt)mentioning
confidence: 88%
“…As shown in the titration curve, there was no indication of residual bicarbonate since no buffering capacity was observed at the pH range of 6.0-4.0 (Figure 2). While the ammonium oxidation rate was also slowed down at this low pH (Figure 3), likely due to the low bicarbonate availability [23] or possibly due to partial inhibition by FNA [2,24], complete nitritation was still achieved with the gradual bicarbonate dosing used in this study.…”
Section: Performance Of the Ph Controllermentioning
confidence: 75%
“…It has been reported that, at parts per billion (ppb) levels, FNA has inhibitory effects on: 1) the anabolic and catabolic activities of ammonia and nitrite oxidising bacteria [2,3]; 2) growth, nitrate and nitrite reduction activities of denitrifying bacteria in activated sludge [4] and 3) aerobic and anoxic phosphorus uptake by polyphosphate accumulating organisms [5,6]. In addition, FNA has also been shown to inhibit methanogens [7], pathogens [8] and yeast [9].…”
Section: Introductionmentioning
confidence: 99%
“…At alkaline pH values, the availability of NH 3 is not limited and this would be favorable for nitrification considering that NH 3 is the substrate for AMO (Suzuki et al, 1974). However, it is also known that high concentrations of free ammonia inhibit nitrification (Anthonisen et al, 1976;Vadivelu et al, 2006b). In aerobic nitrifying reactors operated under constant aeration and agitation, NH 3 can be lost from the system by volatilization.…”
Section: Environmental Factors Affecting Nitrificationmentioning
confidence: 99%
“…It has been observed that high concentrations of nitrite can inhibit the nitrification process and that could be mainly related to the pH values through the formation of HNO 2 . Nitrous acid is known to inhibit nitrification, thus, low pH values must be avoided in nitrifying processes (Anthonisen et al, 1976;Vadivelu et al, 2006aVadivelu et al, , 2006b. Recently, Silva et al (2011) reported that the nitrite-oxidizing process was more sensitive to the presence of nitrite than the ammonium-oxidizing process, suggesting that nitrite accumulation in nitrification systems should be controlled to avoid a higher accumulation of nitrite and a decrease in nitrate yield.…”
Section: Environmental Factors Affecting Nitrificationmentioning
confidence: 99%